Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd007302
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin for refractory partial epilepsy

Abstract: This review of randomised controlled trials shows that vigabatrin can reduce seizure frequency in people with drug-resistant partial epilepsy. Short-term follow up of patients shows some side effects are associated with its use. Further analysis of longer term observational studies is required to evaluate how likely patients are to develop visual field defects, and whether such side effects are associated with dose and duration of drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In the most severe cases, uncontrolled CPS can lead to death from various causes including accidents or SUDEP (sudden unexplained death in someone with epilepsy), a condition where no underlying cause other than epilepsy can be identified [4]. Partial seizures are the seizure type most likely to be refractory to treatment [5]. Several drugs are approved for the initiation of treatment of CPS in the USA, including carbamazepine, phenytoin and valproic acid/divalproex sodium, and many others have been employed as adjunctive therapy.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most severe cases, uncontrolled CPS can lead to death from various causes including accidents or SUDEP (sudden unexplained death in someone with epilepsy), a condition where no underlying cause other than epilepsy can be identified [4]. Partial seizures are the seizure type most likely to be refractory to treatment [5]. Several drugs are approved for the initiation of treatment of CPS in the USA, including carbamazepine, phenytoin and valproic acid/divalproex sodium, and many others have been employed as adjunctive therapy.…”
Section: Overviewmentioning
confidence: 99%
“…Vesicularized GABA is then released into the synapse after neuronal depolarization by a propagated action potential. Free GABA diffuses to the [4,5,7,9,[84][85][86][87][88][89] Pharmaprojects -Copyright to Citeline Drug Intelligence (an Informa business). Readers are referred to Informa-Pipeline (http://informapipeline.citeline.com) and Citeline (http://informa.citeline.com).…”
Section: The Gaba Systemmentioning
confidence: 99%
“…Four studies were performed in drug-resistant partial epilepsy, 5 in psychiatric disorders (4 in generalized anxiety disorder and 1 in social anxiety disorder), 3 in fibromyalgia, and 10 in neuropathic pain. Mean duration of studies was 13 weeks (range [12][13][14][15][16][17] for studies performed on epilepsy, 7 weeks (range 4-10) for psychiatric disorders, 12 weeks (range [8][9][10][11][12][13][14] for fibromyalgia, and 10 weeks (range 4-14) for neuropathic pain. Characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their widespread use, a comprehensive understanding of their tolerability profile is still lacking. Meta-analyses of randomized controlled trials (RCTs) of AEDs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have attempted to bridge this knowledge gap, but their assessment of AED toxicity has been hampered by sample size limitations due to exclusion of studies performed outside of a selected disorder (particularly epilepsy).…”
Section: Introductionmentioning
confidence: 99%
“…In a Cochrane meta-analysis of 11 clinical trials of vigabatrin in the treatment of partial epilepsy, patients treated with vigabatrin were significantly more likely to obtain a 50% or greater reduction in seizure frequency compared with those treated with placebo (RR 2.58, 95% CI 1.87-3.57) [86]. Vigabatrin has been increasingly used in the treatment of infantile spasms as an alternative to hormonal treatment.…”
Section: Efficacymentioning
confidence: 99%